Analisis Perilaku dan Kebutuhan Remaja dalam Peningkatan Kesehatan Remaja di Kota Makassar - Muliani Ratnaningsih; Muhammad Rustam; Munadhir Munadhir; Hajra Hajra (Dian Nuswantoro Semarang, 2023)
Background: PKPR or adolescents friendly health services is a health service for adolescents and can be accessed by adolescents anywhere in Indonesia. In 2014, South Sulawesi, out of 90% of the program target of each district/city that is capable of implementing PKPR, currently only 62.5%. By the end of 2019, it is targeted that 45% of public health centers throughout Indonesia have organized youth health activities. Objectives: Analyzed the implementation of national standards for PKPR services based on five national standards for adolescents care health services, (1) Human resources in health; (2) Health facilities; (3) Youth; (4) Networks; and (5) Health Management in the health center, Makassar. Method: This type of research is a qualitative descriptive with a cross-sectional study. The interviewed informants were 12 puskesmas officers and 1 staff from the Family Health Division of Health Office. The sampling technique used purposive sampling by making criteria. Results: 11 out of 13 references stated that those implementing the PKPR were health workers. 3 out of 12 references stated that the number of trained health workers for PKPR is still small, because of the double burden of work or programs that must be handled by health workers. 10 out of 13 reference answers stated that adolescents' health service package implemented was still related to nutrition and reproductive health. Conclusion: The evaluation of the implementation of the National Standard for PKPR has been implementing in the health center. The best national standards have been implemented, was first standard (human resources in health) and second standard, health facilities, which can be described by the implementation of services inside and outside the building for educational activities to adolescents. The implementation of PKPR that has not been maximally implemented is standard 3 (youth), standard 4 (network), and standard 5 (health management).